Effect of Municipal Solid Waste Compost on Antimony Mobility, Phytotoxicity and Bioavailability in Polluted Soils - Stefania Diquattro; Giovanni Garau; Matteo Garau; Gian Paolo Lauro; Maria Vittoria Pinna; Paola Castaldi (Soil Systems, 2021)
The effect of a municipal solid waste compost (MSWC), added at 1 and 2% rates, on the mobility, phytotoxicity, and bioavailability of antimony (Sb) was investigated in two soils (SA: acidic soil; SB: alkaline soil), spiked with two Sb concentrations (100 and 1000 mg kg−1). The impact of MSWC on microbial activity and biochemical functioning within the Sb-polluted soils was also considered. MSWC addition reduced water-soluble Sb and favored an increase in residual Sb (e.g., by 1.45- and 1.14-fold in SA-100 and SA-1000 treated with 2% MSWC, respectively). Significant increases in dehydrogenase activity were recorded in both the amended soils, as well as a clear positive effect of MSWC on the metabolic activity and catabolic diversity of respective microbial communities. MSWC alleviated Sb phytotoxicity in triticale plants and decreased Sb uptake by roots. However, increased Sb translocation from roots to shoots was recorded in the amended soils, according to the compost rate. Overall, the results obtained indicated that MSWC, particularly at a 2% rate, can be used for the recovery of Sb-polluted soils. It also emerged that using MSWC in combination with triticale plants can be an option for the remediation of Sb-polluted soils, by means of assisted phytoextraction.